Pemberontakan Gunarto: Analisis Tokoh Anak dalam Ayahku Pulang dari Perspektif Psikologi Remaja - Wisnu Samodro (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The drama Ayahku Pulang is able to describe Indonesian families during the colonial era. This story is very stressful between family members. One of the people who experiences the most spiritual turmoil is Gunarto, a young man who is now an adult. Gunarto shows a tough, cynical nature, and does not accept his parents back who are no longer worthy of being his mainstay. In this context, the character of Gunarto is a very interesting literary object for research among teenagers. His position is so important for research on adolescent psychology because at this time they are in the midst of an identity crisis, regarding the search for identity. The purpose of this study is to analyze the character of Gunarto as a representation of the inner conflict of adolescents in the drama Ayahku Pulang using Erikson's development theory. According to Eriksonian theory, adolescence is in search of identity through protest against wrong roles. Gunarto in this case is compared with a character who not only faces external conflict in his relationship with his father, but also internal conflict about the child's self-awareness, feelings of disappointment, and the need for emotional stability. The method used in this study is a qualitative method with drama text analysis techniques. Data obtained from the original manuscript of Ayahku Pulang were analyzed descriptively-analytically to explore the dynamics of Gunarto's psychology holistically. From this study, the importance of understanding the psychology of adolescence in literary works, especially when it comes to the relationship between parents and children. Gunarto's character is the voice of a wounded youth. This study focuses on literary psychology and is codified in Indonesian families. This scope opens up criticism of the role and how consistent the parental figure is in developing the identity of the younger generation.